1993
DOI: 10.1093/hmg/2.2.97
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of the X-linked glycerol kinase deficiency gene and its identification by sequence comparison to the Bacillus subtilis homologue

Abstract: cDNA clones from a human adult testis cDNA library were isolated and sequenced as part of a programme to produce expressed sequence tags (ESTs). ESTs were used routinely to search DNA and protein sequence databases. One clone (142) showed 60% identity to the Bacillus subtilis glycerol kinase gene at both the DNA and amino acid sequence levels. Analysis of DNA from somatic cell hybrids carrying deleted X chromosomes, has shown that clone 142 detects homologous sequences between Xp21.2-p22.1 (the interval contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…The highest level of mammalian GyK activity is typically found in renal and hepatic tissues; a lower level of activity is also detectable in brain, intestine, muscle, adrenal gland, fat, and, in some species, sperm (Lin, 1977;Thorner and Paulus, 1973). The GyK protein is highly conserved throughout evolution as reflected by the high degree of protein sequence identity maintained between bacteria and humans (Sargent et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The highest level of mammalian GyK activity is typically found in renal and hepatic tissues; a lower level of activity is also detectable in brain, intestine, muscle, adrenal gland, fat, and, in some species, sperm (Lin, 1977;Thorner and Paulus, 1973). The GyK protein is highly conserved throughout evolution as reflected by the high degree of protein sequence identity maintained between bacteria and humans (Sargent et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The hGK cDNA was cloned independently by three groups [Guo et al, 1993;Sargent et al, 1993;Walker et al, 1993]. In addition, Sargent et al [1994] reported part of the genomic organization of the Xp21 GK.…”
Section: Discussion Genomic Organization Of Gk Genementioning
confidence: 99%
“…The gene for GKD was first localized to Xp21.3 by cytogenetic and molecular analysis of patients with the contiguous gene syndrome [McCabe, 1999]. The GK gene was isolated and the cDNA was cloned independently by three groups [Guo et al, 1993;Sargent et al, 1993;Walker et al, 1993]. This gene was reported to contain 19 exons and to be more than 50 kb in size, while the GK genes on chromosomes 1, 4, and Xq were intronless [Sargent et al, 1994].…”
Section: Introductionmentioning
confidence: 99%
“…These observations demonstrate that only the partial sequencing associated with sequence comparison was able to establish a link among those genes. This is an efficient way to characterize new human genes as done for the human isologs of yeast suiI [25] and CDC10 [26] or for human genes involved in genetic diseases such as hereditary colon cancer [27] or X-linked glycerol kinase deficiency [28].…”
Section: Discussionmentioning
confidence: 99%